Answer:
153938040.0259 ft2
Step-by-step explanation:
R= Square root of A/π
Answer:
153,860,000 ft^2.
Step-by-step explanation:
The area = 3.14 * r^2
= π * 7,000^2
= 153,860,000 ft^2.
A square base of a pyramid has the dimensions 5 yards by 5 yards. The height of one of the triangular faces is 12 yards. How can you find the surface area of the pyramid?
Answer:
145 yards squared
Step-by-step explanation:
So the area of the base is area of a square with side length of 5 yards [tex]5*5=25[/tex]
The area of one triangular face base times height divided by two and then simply multiplied by 4 because there are 4 triangular faces.
[tex](\frac{5*12}{2} )*4 = 120[/tex]
So the total surface area is [tex]25+120=145[/tex] yards squared
Answer:
First, draw and label a net of the pyramid. The triangular faces have a base of 5 yards and a height of 12 yards. Find the area of each of the faces. The square base has an area of 25 yd2. Each of the triangular faces has an area of 30 yd2. Add the areas together to find the surface area: 25 + 30 + 30 + 30 + 30 = 145 yd2.
Step-by-step explanation:
Which is the true solution to the radical equation y + 1 =
-2y-3?
Need help in number 9. Thanks for helping
Answer:
B.
Step-by-step explanation:
The range is just the list of y-coordinates while the domain is just a list of the x-coordinates when it comes to a list of points.
So anyways all your y-coordinates are -2,-1,0,1,2. So that is your range.
Answer:
B.
Step-by-step explanation:
Solve 2cos theta+2=3 in the interval 0-2pi
Answer:
[tex]\theta=\frac{\pi}{3}, \frac{5\pi}{3}[/tex].
Step-by-step explanation:
[tex]2\cos(\theta)+2=3[/tex]
Subtract 2 on both sides:
[tex]2\cos(\theta)=3-2[/tex]
Simplify:
[tex]2\cos(\theta)=1[/tex]
Divide both sides by 2:
[tex]\cos(\theta)=\frac{1}{2}[/tex]
Now let's refer to the unit circle... When is the x-coordinate, 1/2?
There are 2 places this happens on [0,2pi].
One is in the first quadrant and the other in the fourth quadrant.
It is at [tex]\theta=\frac{\pi}{3}, \frac{5\pi}{3}[/tex].
WILL GIVE BRAINSLIEST EASY. Find each product mentally. Show the steps used.
1. 9 x 44 = 2. 4 x 5 1/8 = 3. 7 x 3.8 =
Use the Distributive Property to rewrite each algebraic expression.
4. 8(x + 7) = 5. 6(11 + x) = 6. 8(x + 1) =
Answer:
1) 396
2) 20 1/2
3) 26.6
4) 8x + 56
5) 66 + 6x
6) 8x + 8
Step-by-step explanation:
* Lets explain how to solve the product mentally
# Remember the distributive property can help you to find the product
mentally the distributive property ⇒ a(b + c) = ab + ac
- Lets solve them
1)
- In 9 × 44 we can write 44 as (40 + 4)
∴ 9 × 44 = 9(40 + 4)
∵ 9(40 + 4) = 9 × 40 + 9 × 4
- Now lets multiply 9 by 40 and 9 by 4
∵ 9(40) = 360
∵ 9(4) = 36
∴ 9 × 40 + 9 × 4 = 360 + 36 = 396
∴ 9 × 44 = 396
2)
- In 4 × 5 1/8 we can write 5 1/8 as (5 + 1/8)
∴ 4 × 5 1/8 = 4(5 + 1/8)
∵ 4(5 + 1/8) = 4 × 5 + 4 × 1/8
- Now lets multiply 4 by 5 and 4 by 1/8
∵ 4(5) = 20
∵ 4(1/8) = 1/2
∴ 4 × 5 + 4 × 1/8 = 20 + 1/2 = 20 1/2
∴ 4 × 5 1/8 = 20 1/2
3)
- In 7 × 3.8 we can write 3.8 as (3 + 0.8)
∴ 7 × 3.8 = 7(3 + 0.8)
∵ 7(3 + 0.8) = 7 × 3 + 7 × 0.8
- Now lets multiply 7 by 3 and 7 by 0.8
∵ 7(3) = 21
∵ 7(0.8) = 5.6
∴ 7 × 3 + 7 × 0.8 = 21 + 5.6 = 26.6
∴ 7 × 3.8 = 26.6
- The distributive property ⇒ a(b + c) = ab + ac
4)
- In 8(x + 7) we will multiply 8 by x and 8 by 7 and add them
∵ 8 × x = 8x
∵ 8 × 7 = 56
∴ 8(x + 7) = 8x + 56
5)
- In 6(11 + x) we will multiply 6 by 11 and 6 by x and add them
∵ 6 × 11 = 66
∵ 6 × x = 6x
∴ 6(11 + x) = 66 + 6x
6)
- In 8(x + 1) we will multiply 8 by x and 8 by 1 and add them
∵ 8 × x = 8x
∵ 8 × 1 = 8
∴ 8(x + 1) = 8x + 8
F(x)=x^2 What is F(x)+f(x)+f(x)
Answer:
Step-by-step explanation:
F(x)=x^2 What is F(x)+F(x)+F(x) =3F(x) =3x²
Answer:
[tex]F(x)+F(x)+F(x)[/tex] = [tex]3x^{2}[/tex]
Step-by-step explanation:
Given is :
[tex]F(x)=x^{2}[/tex]
We have to find: [tex]F(x)+F(x)+F(x)[/tex]
This means we have to find [tex]x^{2} +x^{2} +x^{2}[/tex]
This becomes [tex]3x^{2}[/tex]
Hence, [tex]F(x)+F(x)+F(x)[/tex] = [tex]3x^{2}[/tex]
Solve the following equation. Then place the correct number in the box provided. 2x - 20 = 32
Answer:
x=26
Step-by-step explanation:
Given:
2x - 20 = 32
2x=32+20
2x=52
2x/2=52/2
x=26!
I need help ASAP please someone help me
Answer:
I know it has nothing to do with Christianity, so C and D are wrong. It's either A or B, but I'm more with the A. But I'm not sure so...
Michael goes to a theme park and rides two different roller coasters that both begin on a raised platform. His height while on the first roller coaster, measured in feet from the platform height, can be modeled by the following graph, where t is the number of seconds since the ride began. His height while on the second roller coaster, measured in feet from the platform height, can be modeled by a trigonometric function, shown in the following table, where t is the number of seconds since the ride began. t 0 20 40 60 80 100 120 140 160 g(t) 0 50 100 50 0 -50 -100 -50 0 Which of the following best describes Michael's height while on the two roller coasters? A. While on the first roller coaster, the function modeling Michael's height switches from positive to negative every 60 seconds, meaning he changes from being at a height above the platform to below the platform every 60 seconds. While on the second roller coaster, this change occurs every 20 seconds. B. While on the first roller coaster, the function modeling Michael's height switches from positive to negative approximately every 40 seconds, meaning he changes from being at a height above the platform to below the platform approximately every 40 seconds. While on the second roller coaster, this change occurs every 80 seconds. C. While on the first roller coaster, the function modeling Michael's height switches from positive to negative every 40 seconds, meaning he changes from being at a height above the platform to below the platform every 40 seconds. While on the second roller coaster, this change occurs every 20 seconds. D. While on the first roller coaster, the function modeling Michael's height switches from positive to negative approximately every 80 seconds, meaning he changes from being at a height above the platform to below the platform approximately every 80 seconds. While on the second roller coaster, this change occurs every 40 seconds.
Answer:
on plato the answer is B, it reads the same as the answer c does on this example. Please make sure that you read the answers and match them up with the correct one on your side.
Step-by-step explanation:
Using the information provided, Michael's height changes from above to below the platform every 40 seconds for the second roller coaster. However, without more concrete information regarding the first roller coaster, a definitive answer for that cannot be provided.
Explanation:The topic in discussion here is the modeling of Michael's height changes on two different roller coasters using functions and graphs. Given the question, we can observe that the second roller coaster's height variations follow a pattern corresponding to a trigonometric function, changing from 0, to 50, to 100, and so forth, then repeating. From this pattern, we can infer that Michael's height on the second roller coaster oscillates from a positive value (above the platform) to a negative value (below the platform) and back every 40 seconds since the value of g(t) changes from positive to negative (or vice versa) at each 40-second interval.
However, without the details of the first roller coaster's function or graph, we cannot accurately determine how often Michael's height on the first coaster changes from positive to negative. Therefore, based on the given information, we cannot definitively choose between the provided answer options.
Learn more about Modeling Height Changes here:https://brainly.com/question/5449909
#SPJ3
Dan took a train to his vacation spot. His train travels 75 miles each hour before making a stop. He left the station at 10:00. Phil is taking a vacation to the same spot, except his train travels 60 miles each hour before making a stop. Phil’s train left the station at 8:00. What time will they be in the same place?
Answer:
6pm
Step-by-step explanation:
Assumption: Both Dan and Phil both depart from the same station and arrive at the same station. (i.e they both travel the same distance)
Dan's travel speed is 75mph and Phil's travel speed is 60mph
Let Dan's travel time be [tex]t_{Dan}[/tex] and Phil's travel time be [tex]t_{Phil}[/tex]
Use Formula Distance travelled = speed x time, hence
Dan's Distance Travelled =75 [tex]t_{Dan}[/tex]
Phil's Distance Travelled =60 [tex]t_{Phil}[/tex]
Because they travel the same distance, we can equate the 2
75 [tex]t_{Dan}[/tex] = 60 [tex]t_{Phil}[/tex]
or [tex]t_{Dan}[/tex] = (60/75) [tex]t_{Phil}[/tex]
[tex]t_{Dan}[/tex] = 0.8 [tex]t_{Phil}[/tex] -------> eq 1
We also know that Dan left at 10:00 and Phil left at 8:00. If they end up being at the same place, this means that Phil's journey will be 2 hours longer than Dan, or
[tex]t_{Phil}[/tex] = [tex]t_{Dan}[/tex] + 2------> eq2
we can solve the system of 2 equations to get
[tex]t_{Phil}[/tex] = 10 hrs
[tex]t_{Dan}[/tex] = 8 hrs
If Phil left at 8:00 am, he will be in the same place as Dan at 8:00 + 10 hrs = 6 pm.
Double Check:
If Dan left at 10:00, he will be in the same place as Phill at 10:00 + 8 hrs = 6 pm.
Classify the polynomial -3x5 by degree.
cubic
quadratic
quintic
constant
Answer:
quintic
Step-by-step explanation:
I will assume you mean
-3x^5
This is to the degree 5, since it is to the 5th power
cubic 3rd power
quadratic 2nd power
quintic 5th power
constant 0th power
Answer:
Quintic polynomial is a polynomial with degree 5
Step-by-step explanation:
[tex]-3x^5[/tex]
Given polynomial has degree 5 . Its a 5th degree polynomial
Cubic polynomial has degree 3
Quadratic polynomial has degree 2
Constant is a polynomial with a number without any variable like 2 or 4 or 15
Quintic polynomial is a polynomial with degree 5. Given polynomial has degree 5 . So it is Quintic
Help ASAP pls !!!!!!!!!!!!!
Answer:
I think it's B.
Step-by-step explanation:
They are asking for integers greater than -3 and less than 5.
For this case we have to:
[tex]x <-3[/tex]: Represents the solution of all strict minor numbers to -3.
[tex]x> 5[/tex]: Represents the solution of all strict major numbers to 5.
The global solution is given by the intersection of both sets.
If we represent the solution in a straight line, it gives us empty. do not intersect.
Answeer:
Option C
If f = {(4, 2), (6, 1), (8, 4), (10, 2), (12,5)}, what is the range?
Range means all the y values included on the function/relation on the graph. In this case the y values/range is:
{1, 2, 4, 5}
^^^Remember to order them from smallest to largest and to a number only once if there are more then one of that number included in the range.
Hope this helped!
~Just a girl in love with Shawn Mendes
Could anyone answer and also provide explanation.
Answer:
b
Step-by-step explanation:
The equation of a line in slope- intercept form is
y = mx + c ( m is the slope and c the y- intercept )
(a)
2x + 3y = 1 ( subtract 2x from both sides )
3y = - 2x + 1 ( divide all terms by 3 )
y = - [tex]\frac{2}{3}[/tex] x + [tex]\frac{1}{3}[/tex] ← in slope- intercept form
with y- intercept c = [tex]\frac{1}{3}[/tex] ← does not pass through the origin
(b)
2x + 3y = 0 ( subtract 2x from both sides )
3y = - 2x + 0 ( dividing all sides by 3 ), gives
y = - [tex]\frac{2}{3}[/tex] x + 0 ← in slope- intercept form
with y- intercept c = 0 ← passes through the origin
(c)
2x + 3y = 6 ( subtract 2x from both sides )
3y = - 2x + 6 ( divide all terms by 3 )
y = - [tex]\frac{2}{3}[/tex] x + 2
with y- intercept c = 2 ← does not pass through the origin
What is the inverse of the function f(x) = 2x + 1?
Answer:
The inverse f-1(x) = ( x - 2) / 2.
Step-by-step explanation:
Let 2x + 1 = y
Now find x in terms of y:
2x = y - 1
x = (y - 1) / 2
Replace the x by the inverse f-1(x) and the y by x, so we have:
f-1(x) = ( x - 2) / 2.
[tex]f(x)=2x+1\\\\y=2x+1\\2x=y-1\\x=\dfrac{y-1}{2}\\\\f^{-1}(x)=\dfrac{x-1}{2}[/tex]
Tracey pays $18 to enter a theme park, plus $2 for each ride. Which of the following correctly describes the slope? A. she must pay a flat rate of $18. B. Her total cost increases by $2, for each ride purchased. C. Her total cost is at least $20. D. her total cost increased by $3, for each ride purchased
Answer:
B.
Step-by-step explanation:
You pay a one time fee of 18 dollars and then 2 dollars per ride.
The expression for that is 18+2r where r represents the number of rides and the output of (18+2r) is amount you spend.
f(r)=2r+18 when compared to f(x)=mx+b where m is slope and b is y-intercept
you should see that the slope is $2 per ride.
B. is the option that says this.
Answer: Option B
Her total cost increases by $2, for each ride purchased
Step-by-step explanation:
We know that $ 18 is the cost of the ticket. We do not know exactly how many trips you will make, but we know that the cost is $ 2 for each ride.
If we call "x" the number of rides then we know that the total cost "y" is:
[tex]y = 2x + 18[/tex]
Note that the cost increases by $2 for each ride
The equation of a line has the following form
[tex]y = mx + b[/tex]
Where m is the slope of the line.
In this case we have the following equation
[tex]y = 2x + 18[/tex]
Therefore [tex]m = 2[/tex]. Then the slope is the cost of $2 for each ride
Finally the answer is the option B. Her total cost increases by $2, for each ride purchased
Which of the following are solutions to the equation below?
Check all that apply.
5x2 - 2x + 16 = 4x2 + 6x
O A. -6
O B. 6
O C.-3
D. -4
E 4
O
F. 18
Answer:
E. x = 4Step-by-step explanation:
[tex]5x^2-2x+16=4x^2+6x\qquad\text{subtract}\ 4x^2\ \text{from both sides}\\\\x^2-2x+16=6x\qquad\text{subtract}\ 6x\ \text{from both sides}\\\\x^2-8x+16=0\\\\\text{Put the values of}\ x\ \text{to the equation and check the equality:}\\\\A.\ x=-6\\\\(-6)^2-8(-6)+16=36+48+16=100\neq0\\\\B.\ x=6\\\\6^2-8(6)+16=36-48+16=4\neq0\\\\C.\ x=-3\\\\(-3)^2-8(-3)+16=9+24+16=49\neq0\\\\D.\ x=-4\\\\(-4)^2-8(-4)+16=16+32+16=64\neq0\\\\E.\ x=4\\\\4^2-8(4)+16=16-32+16=0\\\\F.\ x=18\\\\18^2-8(16)+16=324-128+16=212\neq0[/tex]
Answer:
E
Step-by-step explanation:
Find an equation for the line perpendicular to y=−15x+3 with x-intercept at x = 3.
Write your answer in the form y=mx+b
bearing in mind that perpendicular lines have negative reciprocal slopes, let's find the slope of the provided line then
[tex]\bf y=\stackrel{\stackrel{m}{\downarrow }}{-15}x+3\qquad \impliedby \begin{array}{|c|ll} \cline{1-1} slope-intercept~form\\ \cline{1-1} \\ y=\underset{y-intercept}{\stackrel{slope\qquad }{\stackrel{\downarrow }{m}x+\underset{\uparrow }{b}}} \\\\ \cline{1-1} \end{array} \\\\[-0.35em] ~\dotfill[/tex]
[tex]\stackrel{\textit{perpendicular lines have \underline{negative reciprocal} slopes}} {\stackrel{slope}{-15\implies -\cfrac{15}{1}}\qquad \qquad \qquad \stackrel{reciprocal}{-\cfrac{1}{15}}\qquad \stackrel{negative~reciprocal}{+\cfrac{1}{15}\implies \cfrac{1}{15}}}[/tex]
well, we know the x-intercept is at x = 3, recall when a graph intercepts the x-axis y = 0, so this point is (3 , 0). Then we're really looking for the equation of a line whose slope is 1/5 and runs through (3 , 0).
[tex]\bf (\stackrel{x_1}{3}~,~\stackrel{y_1}{0})~\hspace{10em} slope = m\implies \cfrac{1}{5} \\\\\\ \begin{array}{|c|ll} \cline{1-1} \textit{point-slope form}\\ \cline{1-1} \\ y-y_1=m(x-x_1) \\\\ \cline{1-1} \end{array}\implies y-0=\cfrac{1}{5}(x-3)\implies y=\cfrac{1}{5}x-\cfrac{3}{5}[/tex]
In right triangle ABC, B is the right triangle and m C = 30. If AC = 10 what is AB?
Using the law of sins:
Sin(angle) = Opposite Leg / Hypotenuse
Sin(30) = AB /10
Solve for AB:
AB = 10 * sin(30)
AB = 10 * 1/2
AB = 5
The answer is A.
Select the correct answer from each drop-down menu.
consider the equation
-22 + 3x
___________ = 2
3x + 7
How do you begin isolating the variable x to one side of the equation?
A) Multiply both sides by 3x + 7.
Reset
B) Divide both sides by 3x + 7.
C) Multiply both sides by -22 + 3x.
D) Divide both sides by -22 + 3x.
The solution of the equation is
A) -12
B) -9
C) -6
D) -3
Answer:
A)Multiply both sides by 3x + 7.
Reset
A)the solution of the equation is x=-12
Step-by-step explanation:
Hello
let
to begin isolating we must multiply both sides by 3x + 7.
Reset
this way
[tex]\frac{-22+3x}{3x+7}=2\\\frac{-22+3x}{3x+7}*(3x+7)=2*(3x+7)\\-22+3x=2*(3x+7)[/tex]
let´s continue to find x
[tex]\\-22+3x=2*(3x+7)\\-22+3x=6x+14\\-22-14=6x-3x\\-36=3x\\x=\frac{-36}{3}\\ x=-12[/tex]
the solution of the equation is x=-12
have a great day
A, B, and C are polynomials, where A = n, B = 2n + 6, and C = n2 – 1. What is AB – C in simplest form?
Answer:
B=n2 + 6n + 1
Step-by-step explanation:
A = n
B = 2n + 6
C = n^2 - 1
AB - C = n * (2n + 6) - (n^2 - 1) = 2n^2 + 6n - n^2 + 1 = n^2 + 6n + 1
Answer:
The simplest form of the expression AB-C is [tex]n^2+6n+1[/tex].
Step-by-step explanation:
In this exercise we only need to use the properties of arithmetic operations and a minimal knowledge of algebraic notation. We have the expressions
[tex]A = n[/tex],[tex]B=2n+6[/tex],[tex]C=n^2-1[/tex].Now we make the indicated operations, beginning by AB:
[tex]AB=n\cdot(2n+6) = 2n^2+6n[/tex] using the distributive property of multiplication.
Then, we make AB-C:
[tex]AB-C = 2n^2+6n - (n^2-1) = 2n^2+6n-n^2+1 = n^2+6n+1[/tex].
In the last step we must be vary careful with the change of signs in the expression inside parenthesis.
PLEASE HELPP!!
The graph of y = ax^2 + bx + c is shown below. Determine the solution set of 0 = ax^2 + bx + c.
Check the picture below.
something noteworthy to look at is that the graph doesn't cross the x-axis at -2, it simply comes down to it, touches it and it goes back up, it simply bounces off the x-axis, whenever that happens, that zero/solution/root has an even multiplicity.
when 0 = ax² + bx + c, we notice that y = 0, and for the graph that happens there, at x = -2, but that solution has an even multiplicity, and since the equation is a 2nd degree polynomial, thus x = -2 is there twice, namely
x = -2
x - 2 = 0
(x - 2)² = 0 <---- multiplicity of 2.
Answer:
-2
Step-by-step explanation:
:)
17
Find the x-intercepts of the parabola with vertex (1,-9) and y-intercept at (0,-6).
A. (-1,0), (3,0)
B. (-0.73,0), (2.73,0)
C. (-1.48,0), (2.48,0)
D. (-4.67,0), (1.67,0)
let's firstly find the equation of the parabola, bearing in mind that x-intercepts or solutions/zeros/roots means y = 0.
[tex]\bf ~~~~~~\textit{vertical parabola vertex form} \\\\ y=a(x- h)^2+ k\qquad \begin{cases} \stackrel{vertex}{(h,k)} \end{cases} \\\\[-0.35em] \rule{34em}{0.25pt}\\\\ \begin{cases} h=1\\ k=-9 \end{cases}\implies y=a(x-1)^2-9 \\\\\\ \textit{we also know that } \begin{cases} x=0\\ y=-6 \end{cases}\implies -6=a(0-1)^2-9\implies 3=a(-1)^2[/tex]
[tex]\bf 3=a\qquad \qquad \textit{therefore}\qquad \qquad \boxed{y=3(x-1)^2-9} \\\\[-0.35em] ~\dotfill\\\\ \stackrel{y}{0}=3(x-1)^2-9\implies 9=3(x-1)^2\implies \cfrac{9}{3}=(x-1)^2\implies 3=(x-1)^2 \\\\\\ \pm\sqrt{3}=x-1\implies \pm\sqrt{3}+1=x\implies x= \begin{cases} \sqrt{3}+1\\ -\sqrt{3}+1 \end{cases}\implies x\approx \begin{cases} 2.73\\ -0.73 \end{cases}[/tex]
Graph y=lx-3l please answer fast
Answer:
(see attachment)
Step-by-step explanation:
With an absolute value graph, if the number is inside the brackets you move the graph in the opposite direction.
(Btw you should use Desmos. That's what I use all the time and it is a LIFESAVER)
(Also can I please have Brainliest, I need it to level up)
The graph of the function y = |x - 3| is added as an attachment
Sketching the graph of the functionFrom the question, we have the following parameters that can be used in our computation:
y = |x - 3|
The above function is an absolute function that has been transformed as follows
Vertically stretched by a factor of 1Shifted right by 3 unitsNext, we plot the graph using a graphing tool by taking not of the above transformations rules
The graph of the function is added as an attachment
Read more about functions at
brainly.com/question/2456547
#SPJ2
Les tried to evaluate 600 x 4 step by step.
600 X 4
Step 1
= 10 x 6 x 4
Step 2
= 10 x 24
Step 3
= 240
Find Les's mistake.
Choose 1 answer:
@ Step 1
B Step 2
C Step 3
DLes did not make a mistake.
Answer:
A Step 1
Step-by-step explanation:
600 X 4
6*100 *4
The mistake is in the first line
600 = 6*100 not 6*10
what is (7x6)+(4x10)
Answer:
the answer is 82
Step-by-step explanation:
Answer:
82
Step-by-step explanation:
just use a calculator
Find the length of CZ
Think for a minute.
CA = 17, right?
CZ is the remaining part of CA.
ZA = 16
CZ = CA - ZA
CZ = 17 - 16
CZ = 1
Did you follow?
Answer:
D 1
Step-by-step explanation:
CA = CZ + ZA
WE know CA = 17 and ZA = 16
17 = CZ + 16
Subtract 16 from each side
17-16 = CZ +16-16
1 = CZ
Which formula gives the area of a parallelogram? (3)
Answer:
A = bh (the last one)
Step-by-step explanation:
To find the area of a parallelogram, multiply the base by the height. The formula is: A = B * H where B is the base, H is the height, and * means multiply. The base and height of a parallelogram must be perpendicular.
Answer:
A=bh
Step-by-step explanation:
There are 321 visitors at the library. Each library table seats 12 people. How many tables are needed to seat all of the visitors?
(Explain the process of how you got your answers)
Hello.
The answer is: 27
To get this answer you can divide 321 and 12. But that will give you an uneven number such as 26.75. And because you cant have 26.7 tables you will wound it up to be 27 tables.
Answer:
321÷12=26.75
answer: 27
Step-by-step explanation:
since you know that each table can only seat 12 people and there is 321 visitors you divide 321 by 12 which you get 26.75, but u cant have 26.75 tables so you round up to 27 so you can seat all the visitors because if you round down to 26, 9 people won't have a seat.
Which fact helps you prove the isosceles triangle theorem, which states that the base angles of any isoceles triangle have equal measure?
Answer:
If one angle of a triangle is larger than another angle, then the side opposite the larger angle is longer than the side opposite the smaller angle.
Step-by-step explanation:
The fact that one angle of a triangle is larger than the other angle and the side that is opposite the larger angle is longer than the side which is opposite the smaller angle proves the isosceles triangle theorem.
This theorem proves that the base angles of any isosceles triangle have equal measure.
If one angle of a triangle is larger than another angle, then the side opposite the larger angle is longer than the side opposite the smaller angle.
e2020